LINGKUNGAN KERJA MEMODERASI KOMITMEN ORGANISASIONAL DAN MOTIVASI TERHADAP KINERJA GURU SMP SWASTA BERBASIS ISLAM SUB RAYON 03 DI KOTA SEMARANG - Kustiyono, 11.52.02.0003 (Students Journal of Economic and Management, 2013)
This study aims to examine and describe the influence of: (1) organizational commitment on teacher performance, (2) motivation on teacher performance, (3) the working environment on teacher performance, (4) the working environment in moderating the organizationals commitment to teacher performance, and (5 ) the working environment in moderating teacher motivation on performance. This research is explanatory research. The population in this study was 139 teachers at SMP Islam-based Private Sub Rayon 03 in Semarang, amounting to 139 people. The instrument used in the data collection was a questionnaire using a Likert scale, each of which had been tested in compliance with the requirements of validity and reliability and factor analysis and Cronbach Alpha test assumptions Classic. The technique uses test data analysis of multiple linear regression analysis models. R2 test, F test, and hypothesis testing using t-test, and test moderation. The results of the research prove that: (1) organizational commitment have a positive and significant impact on the performance of teachers, (2) motivation positive and significant effect on the performance of teachers, (3) the working environment has positive and significant impact on teacher performance, (4) the working environment is not moderate influence of organizational commitment on teacher performance, (5) the working environment moderate the effect of motivation on teacher performance. Keywords:Working Environment, Organizational Commitment, Motivation, and Teacher performance.